Empirical investigation of the relationship between public external debt sustainability, foreign reserves and fixed exchange rate - Fatima-Ezzahra Rafie; Mostafa Lekhal (Cogent Economics & Finance)
Public external debt sustainability is a critical concern, yet existing frameworks often fail to account for the unique challenges faced by lower-middle-income countries (LMICs) in Africa. These nations, heavily reliant on foreign-currency borrowing, contend with exchange rate volatility, limited access to international markets, and the availability of foreign reserves, all of which compound solvency and liquidity risks. This study addresses this gap by adapting the cointegration method, originally designed for the US context, to assess debt sustainability in LMICs. Specifically, it examines five African LMICs- Morocco, Egypte, Tunisia, Benin, and Senegal – during the period 2000–2021. Benin and Senegal, as members of the Western African Economic and Monetary Union (WAEMU), face additional constraints due to a shared currency, while Morocco, Egypt, and Tunisia have control of their respective monetary policies and manage their reserves. Using unit root tests, Johansen cointegration tests, and a Vector Error Correction Model (VECM), the study investigates the interplay among external debt, reserves, exchange rate, GDP growth, exports, and government expenditures. Findings reveal that while public external debt in these countries experiences short-term fluctuations, it tends to stabilize in the long-term through fiscal and monetary policies. Additionally, foreign reserves significantly influence debt positions, and the exchange rate arrangements adopted in Morocco, Egypt, and Tunisia reduce currency depreciation risks. Conversely, the common currency constraints debt sustainability in Benin and Senegal.